Pengaruh dyadic coping terhadap kepuasan pernikahan pada pasangan menikah di Tangerang - Dermawan, Soesanto; Goei, Yonathan Aditya; Kirana, Kartika Chandra (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2015)
Marital satisfaction is one of the important topics in marital research, because marital satisfaction has major influence on marital stability. One factor that affects marital satisfaction is dyadic coping. This study tested the effect of positive and negative dyadic coping on marital satisfaction. Data was gained from 115 couples. Actor-Partner Interdependence Model (APIM) was used to guide the analysis and calculation was done with multiple level regression. The result indicated significance actor effects from both positive dyadic coping and negative dyadic coping on marital satisfaction. However, none of partner effect was found significant.